Pengaruh Kecerdasan Emosional Terhadap Kinerja Karyawan Melalui Stres Kerja dan Komitmen Organisasional PT. GIU - Uliana Arsi; Muhammad Anhar (Jurnal Riset Manajemen dan Bisnis, 2024)
This study aims to identify and determine the effect of emotional intelligence on work stress, the effect of emotional intelligence on organizational commitment, the effect of work stress on employee performance, the effect of organizational commitment on employee performance, emotional intelligence on employee performance through work stress, the effect of emotional intelligence on employee performance through organizational commitment, the effect of emotional intelligence on employee performance, and analyze the implications of research findings so that they can be applied in the context of human resource management and employee development at PT. GIU to improve employee performance. The method used in this study is a quantitative survey method. The data obtained are primary data from distributing questionnaires to respondents. The population in this study were all employees of PT. Greentex Indonesia Utama from various divisions who are still actively working. Based on the results of calculations using the Slovin formula, the number of samples in this study was 187 people. Determination of the number of samples in this study was by using purposive sampling. The data obtained were processed using SmartPLS 3.0. Statistical analysis of data in this study was descriptive data analysis, outer model analysis, inner model analysis and hypothesis testing. The results of this study indicate that there is a positive and significant influence of emotional intelligence on work stress, there is a positive and significant influence of emotional intelligence on organizational commitment, there is no influence of work stress on employee performance, there is a positive and significant influence of organizational commitment on employee performance, there is no influence of emotional intelligence on employee performance through work stress, there is a positive and significant influence of emotional intelligence on employee performance through organizational commitment, there is a positive and significant influence of emotional intelligence on employee performance. While the implications of this study in the context of human resource management (HR) and employee development at PT. Greentex Indonesia Utama, namely PT. Greentex Indonesia Utama can improve employee performance by providing training and development programs that focus on strengthening emotional intelligence, companies need to create a supportive work environment and provide rewards for employee loyalty and dedication.